BEING, BECOMING AND BREAKING-FREE: PETER MCLAREN AND THE PEDAGOGY OF LIBERATION - Peter McLaren (Ediciones Universidad de Salamanca, 2009)
In this interview, McLaren reflects on different approaches to the field of critical pedagogy and lingers over interpretations derived from the work of Freire, underlining the need to reflect on practice itself in order to find ways which allow oppressed people to become protagonists in history. Likewise, this author states that part of his work is focused on supporting anti-capitalist movements in North America and formulating an alternative to global capitalism, reflecting on the role which critical pedagogy could play in this. He underlines the essential role of teachers in the development of anti-capitalist pedagogies within the heart of today's changing societies, affected by international events such as the election of Obama or the financial crisis, in which schools can become spaces for the production of critical knowledge and for socio-political action.